2012
DOI: 10.1016/j.jpain.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Intensity of TENS Prevents Analgesic Tolerance in Rats

Abstract: Transcutaneous electrical nerve stimulation (TENS) reduces hyperalgesia and pain. Both low frequency (LF) and high frequency (HF) TENS, delivered at the same intensity (90% motor threshold (MT)) daily, result in analgesic tolerance with repeated use by the 5th day of treatment. Thecurrentstudytestedif 1) increasingintensityby 10% per daypreventsthedevelopmentoftolerance to repeated TENS, and 2) iflowerintensity TENS (50 % MT) produces an equivalentreduction in hyperalgesia when compared to 90% MT TENS. Sprague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
0
29
0
3
Order By: Relevance
“…This may explain our 186 findings, showing pain relief throughout a 8 weeks protocol. It is 187 worth reinforcing that variation in intensity and frequency (VIF), 188 present in acupuncture-like TENS used in this study, acts by 189 preventing opioid tolerance generated by a equal intensity current 190 during a prolonged period of electrostimulation [36,37]. On the 191 other hand, variation in intensity and frequency is not included in 192 the self-applied TENS device.…”
Section: Methodsmentioning
confidence: 96%
“…This may explain our 186 findings, showing pain relief throughout a 8 weeks protocol. It is 187 worth reinforcing that variation in intensity and frequency (VIF), 188 present in acupuncture-like TENS used in this study, acts by 189 preventing opioid tolerance generated by a equal intensity current 190 during a prolonged period of electrostimulation [36,37]. On the 191 other hand, variation in intensity and frequency is not included in 192 the self-applied TENS device.…”
Section: Methodsmentioning
confidence: 96%
“…Studies that have evaluated the effect of repeated TENS use have demonstrated tolerance to TENS after five days of repeated application when given at the same dose (frequency and intensity) in healthy human subjects and in animal studies [10,45]. Factors that prolong this tolerance include alternating between low and high frequency [23] and increasing the amplitude over time [62]. While the amplitude was high for all participants in this study, it did not increase over time and high frequency was used throughout.…”
Section: Discussionmentioning
confidence: 99%
“…21 This suggestion is based on animal studies that showed that delayed onset of the analgesic tolerance can be achieved by applying continuous daily increases of the intensity by 10%. 32 However, there is not a full understanding of the tolerance mechanisms in chronic pain owing to the intricacy of the neuronal processing alteration in these patients. 23 Accordingly, owing to the lack of knowledge on the effects of repeated TENS over time in chronic pain as well as in the PD population, 23 we recommend that women who use TENS over a long period should be monitored to detect the development of tolerance.…”
Section: Repeated Usementioning
confidence: 99%